Role of Mathematics Instructors in Enhancing Student’s Self- Confidence in Distance Learning During Coronavirus Disease - Eman Almuhur; Manal Al-labadi; Amani Shatarah; Tala Sasa; Raeesa Bashir; Nazneen Khan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: This article aims to discuss and investigate forms of pedagogical knowledge of mathematicsinstructors and influence of their educational beliefs on their students during Coronavirus disease whereprogress in learning is typically influenced by self-confidence and anxiety.Materials and Methods:A study survey was carried out to find out the extent of anxiety and self-efficiencystudents have before and during mathematics exams in distance learning.Results: Out of 252 students, 88% are females and 12% are males, majority of students of the secondlevel from different faculties filled the survey. The study reveals student’s responses to the levels of thevariables where confident is of ‘always’ attitude with mean 2.3714 (SD=.37764). On the other side, anxietyis of ‘sometimes’ attitude with mean 1.8595(SD=0.4196). Those results are good and indicates that no bigproblems in mathematics either inside or outside university faced by sample we dealt with, this result refersto the simplicity and good characteristics of instructors of the university. Moreover, lots of programs thathelp in understanding basics and advanced mathematics.Conclusion: Successful pedagogies instructors of mathematic used give the best explanation of results wehave got in this study especially in distance learning. Detailed study plan that clarifies the course objectives,topics, evaluation method, books and resources must be given to students.